The Representation of Critical Thinking Dimensions in "English for Nusantara" for Grade 9 Junior High School - Amelya Lucky Diana (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The analysis of the exercises in the English for Nusantara textbook for Grade 9 junior high school showed that most of the exercises were lower-order thinking skills. Out of the 600 exercises, 535 were classified as lower-order thinking skills. The remaining 65 exercises were classified as higher-order thinking skills. The details were analyzed 6 (1%) exercises, evaluated 7 (1.17%), and created (8.67%). Rahpeyma and Khoshmood (2015) explained that the predominance of lower-order thinking skills exercises over higher-order thinking skills exercises was due to the authors’ consideration that students were beginner English learners, assuming they could not handle the difficulty of the higher-order thinking skills exercises. Therefore, the author provided more lower-order thinking skills exercises to help them learn the basics and build a foundation for their English language knowledge. Therefore, based on the findings of this study, it is recommended that the textbook writers adjust the appropriate proportions for each critical thinking dimension to ensure a balanced number of exercises. Teachers need to be more active and creative in addressing these issues, including providing higher-order thinking skills learning activities outside of textbook material. However, this study still had limitations. First, it did not use inter-rater verification and was conducted manually by the researcher. Although action verbs were used to minimize bias, the potential for subjectivity remained. This study focused on a single textbook and did not include other textbooks. Therefore, future researchers can conduct a study on the same topic by involving more than one assessor, using more than one source book from different publishers, or conducting more in-depth qualitative research, such as interviews.
Entry oleh Arif 2026 Januari 30
Keywords: Critical Thinking Dimensions; English for Nusantara; Grade 9 Junior High School